No longer the only game in town: British indies, podcasts and the new audio economy of independent production. Issue 1 (1st April 2021) - Berry, Richard
The world of audio is undergoing seismic changes. Traditionally a space dominated by linear radio programmes, in the 2020s this form of listening remains relevant but is now being challenged by other forms and global media platforms. In particular, podcasting offers producers opportunities to pitch for commissions from brands and platforms or to make work independently. Historically, podcasting was a medium led and shaped by amateurs and distributed for free by independent creators. In the 2020s this relationship began to shift. In the United Kingdom, audio producers are now finding success outside of radio, in what was once a market dominated by the BBC. Forming what we might term a 'new audio economy', producers and creatives are working across multiple forms of production in the long tail of audio media. Through interviews and analysis, this article will explore the impact of podcasting and other forms of audio production on the UK-independent radio/audio sector, noting the influence of the BBC and shifting patterns of production within the sector